विद्यार्थी राजनीतिमा छात्रा सहभागिताको अवस्था {The condition of female student participation in student politics} - त्रिपाठी Tripathi, शकुन्तला Shakuntala (Patan Prospective Journal, 2022)
Available with fulltext.